Conceptual model of continuance intention to use of the Islamic blog / Mohd Nurul Hafiz Ibrahim, Mohd Sazili Mohd Shahibi and Mohamad Noorman Masrek. - Ibrahim, Mohd Nurul Hafiz; Mohd Shahibi, Mohd Sazili; Masrek, Mohamad Noorman (Universiti Teknologi MARA Cawangan Selangor, 2017)
The purpose of this paper is to offer greater insight in the role of content-related factor in the continuance used of the Islamic weblogs as the source of Islamic teachings and practices. Information System (IS) continuance intention Model is being employed as a conceptual tool to re-interpret the existing evidence of the continuance used of the weblogs. Additional elements including credibility, reliability and objectivity are being included to further clarify the role of content-related factor in determining the continued used of the weblogs. The analysis demonstrated that people tend to revisit the weblogs with reliable and credible information. The paper presents the importance of content in terms of credibility, objectivity, and reliability in encouraging people to continue use the Islamic weblogs in disseminating the Islamic information and knowledge significantly influences the people’s intention to revisit the weblogs in future.